KETERKAITAN MODEL PRECEDE PROCEDE TERHADAP BALITA DENGAN STATUS GIZI KURANG DI PUSKESMAS CILACAP UTARA II - Puspitasari, Lina; Mardiah, Nurul Aini (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Toddlers with nutritional status is less a problem of nutritional status on a toddler who is determined from the value of the z-score. Many factors influence the occurrence of nutrition less on toddlers, but still partially examined which means that examined some or one component only. The purpose of the research was to precede proced model interconnectedness knoweth agains toddlers with nutritional status is less in Clinics North of Cilacap II. This research is quantitative research with observational analitic approach of using a case control carried out at the Clinics North II Cilacap. Number of population of 1330 with the total sample as many as 60 people. The technique of sampling is the sampling of fixed disease. The number of cases of 30 groups and a control group of 30. Data collection using the questionnaire. The dependent variables in the study of nutritional status is a toddler less data analysis techniques using path analysi.  Conclusion there is no direct relationship between education with eating patterns, there is a direct relationship between knowledge, family income, the use of clean water, immunization, the regularity of the age of toddlers toward eating patterns toddlers. There is no direct relationship between the behavior of the officers with a toddler eating patterns. There is a relationship between diet nutrition status toddler toddler. Key words: Path analysis, precede procede, eating patterns, nutritional status